Public health impacts of urban traffic jam in sanandaj, Iran: A case study with mixed-method design. (December 2020) - Nadrian, Haidar; Mahmoodi, Hassan; Taghdisi, Mohammad Hossein; Aghemiri, Mehran; Babazadeh, Towhid; Ansari, Bahjat; Fathipour, Asaad
Abstract: Introduction: Our aim was to conduct a health impact assessment (HIA) on Sanandaj urban traffic jam, as a consequence of current urban traffic and transport initiatives conducted by Sanandaj urban traffic and transport system. Methods: Incorporating practice standards into the methodology, and applying a single mixed-method case study, we collected four sources of data through profiling community (archival records/documentations), interviews/focus group discussions, field notes, and community survey in Sanandaj, Iran. Integration of data was conducted at interpretation level (data synthesis). Results: Reviewing archival records, a slight increase was found in the registered death/hospitalization cases due to diseases associated to air pollution. An aggravating trend was found in both air quality of city and fines for traffic violations. Challenges of urban traffic jam from residents' viewpoints were grouped into infrastructural, managerial, sociocultural, psychological and behavioral categories. Essential themes for the health impacts of urban traffic jam included physical and family mental health, and social determinants of health. Community survey showed high levels of negative impacts of urban traffic jam on air quality, public services delivery and accessibility, physical environment, public welfare services, family circumstances, social environment, and tobacco/substance use. The following barriers of urban traffic and transport initiatives were identified as the high priorities for revisiting plans: lack of enough streets/highways, lack of enough underpass/overpass, lack of parking lots in crowded areas and poor traffic education/acculturation. The team of assessors, based on findings, established the priority impacts and recommended justify options for action. Conclusion: Performing the HIA, we portrayed the contribution of a various range of urban-traffic related determinants to public health in a low- and middle-income country (LMIC) setting. This study may recall and familiarize policy and decision makers outside health sector on the ways to provide community health-oriented plans/projects. Our findings are particularly informative for the LMICs, where urban traffic jam is mostly due to poor urban traffic and transport initiatives within urban areas. Highlights: Presents how a mixed-method design may be applied to conduct a Health Impact Assessment (HIA). Turns the spotlight on how urban traffic jam (UTJ) may be a consequence of current urban traffic and transport initiatives. Describes how urban traffic jam underpin quality of life. Highlights the role of health impact assessments prior to implementing the urban traffic and transportation plans.